2016
DOI: 10.3892/etm.2016.3154
|View full text |Cite
|
Sign up to set email alerts
|

Penehyclidine ameliorates acute lung injury by inhibiting Toll-like receptor 2/4 expression and nuclear factor-κB activation

Abstract: Abstract. The aim of the present study was to investigate the effect of penehyclidine (PHC) on endotoxin-induced acute lung injury (ALI), as well as to examine the mechanism underlying this effect. A total of 60 rats were randomly divided into five groups, including the control (saline), LPS and three LPS + PHC groups. ALI was induced in the rats by injection of 8 mg lipopolysaccharide (LPS)/kg body weight. The rats were then treated with or without PHC at 0.3, 1 or 3 mg/kg body weight 1 min following LPS inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…We also observed that Lats2-underexpressing BMSCs improved acute lung inflammation in ALI lung tissue. One of the pathophysiologies of ALI is essentially dysregulated inflammation that manifested by imbalance between proinflammatory and anti-inflammatory response in the lung [36, 37]. Several previous studies indicated that MSCs could enhance the resolution of inflammation in adult ALI patients [16, 35], and sufficient evidence also showed the same modulatory effect: Proinflammatory cytokines such as interferon- γ , IL-1 β , and IL-6 were reduced, while the anti-inflammatory cytokines IL-4 and IL-10 were increased [38].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that Lats2-underexpressing BMSCs improved acute lung inflammation in ALI lung tissue. One of the pathophysiologies of ALI is essentially dysregulated inflammation that manifested by imbalance between proinflammatory and anti-inflammatory response in the lung [36, 37]. Several previous studies indicated that MSCs could enhance the resolution of inflammation in adult ALI patients [16, 35], and sufficient evidence also showed the same modulatory effect: Proinflammatory cytokines such as interferon- γ , IL-1 β , and IL-6 were reduced, while the anti-inflammatory cytokines IL-4 and IL-10 were increased [38].…”
Section: Discussionmentioning
confidence: 99%
“…In both clinical and experimental studies, the drug also moderates infectious and noninfectious inflammation within the respiratory system, possibly by inhibiting Toll-like receptors. [31][32][33][34] Penehyclidine is effective for treatment of acute exacerbations of COPD and acute respiratory distress syndrome, possibly by dilating bronchioles, improving pulmonary compliance, and inhibiting airway inflammation. We therefore tested the hypothesis that inhalation of penehyclidine, a long-acting muscarinic antagonist, reduces a composite of pulmonary complications in high-risk noncardiac surgical patients over the initial 30 postoperative days.…”
Section: Editor's Perspectivementioning
confidence: 99%
“…Experimental and clinical studies report that penehyclidine ameliorates acute lung injury by alleviating inflammation. [31][32][33]50 For example, retrospective analyses report that patients who inhaled tiotropium have lower leukocyte counts and lower C-reactive protein concentrations. 27 It is therefore possible that penehyclidine provides additional lung protection by reducing inflammation, although we did not evaluate this mechanism.…”
Section: Penehyclidine Inhalation and Pulmonary Complicationsmentioning
confidence: 99%
“…Among these hub genes, TLR2 is an inflammation-related receptor that is involved in inflammation-induced diseases, especially that induced by LPS, which serves as a transduction and transmembrane molecule (Wang et al. 2016 ). Key inflammatory cytokines (IL-6 and TNF-α) have been reported to play a key role in the early stage of ALI (Simons et al.…”
Section: Discussionmentioning
confidence: 99%